2017
DOI: 10.1002/srin.201600460
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Chromium from Stainless Steel Slags by NaOH‐Added Pellet Roasting Followed by Water Leaching

Abstract: Preventing toxic Cr 6þ from being eluted from the stainless steel (SSL) slag is still an unsolved problem. An effective extraction of chromium from SSL slag might be a solution. The conventional industrial process in chromium extraction from chromite involves adding Na 2 CO 3 to chromite during the sample roasting. The authors found that if a similar process is used to extract chromium from SSL slag, the chromium extraction was 33% at 800 8C. However, if NaOH is used instead of Na 2 CO 3 , the chromium extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Figure a shows that fluoride leaching efficiency and recovered graphitized carbon purity increased from 96.63 and 95.41% to 96.92 and 96.38%, respectively, with NaOH-to-Na 2 CO 3 mass ratio increased to 20%. This result was attributed to the increasing amount of NaOH with a lower melting point and stronger alkalinity, which improved the fluidity and reactivity of the molten salt system . However, the uniformity of the activated mixture gradually decreased with the increase of NaOH-to-Na 2 CO 3 mass ratio because of the hygroscopicity and viscosity of NaOH.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure a shows that fluoride leaching efficiency and recovered graphitized carbon purity increased from 96.63 and 95.41% to 96.92 and 96.38%, respectively, with NaOH-to-Na 2 CO 3 mass ratio increased to 20%. This result was attributed to the increasing amount of NaOH with a lower melting point and stronger alkalinity, which improved the fluidity and reactivity of the molten salt system . However, the uniformity of the activated mixture gradually decreased with the increase of NaOH-to-Na 2 CO 3 mass ratio because of the hygroscopicity and viscosity of NaOH.…”
Section: Methodsmentioning
confidence: 99%
“…This result was attributed to the increasing amount of NaOH with a lower melting point and stronger alkalinity, which improved the fluidity and reactivity of the molten salt system. 41 However, the uniformity of the activated mixture gradually decreased with the increase of NaOH-to-Na 2 CO 3 mass ratio because of the hygroscopicity and viscosity of NaOH. This view can be supported by the fact that the median particle size of the mixture increased with the increase of NaOH-to-Na 2 CO 3 mass ratio, as shown in Figure S1.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be a separate "reduction furnace" in which valuable metals could be reduced from the slag to very low contents in a properly stirred reactor under highly reducing conditions, e.g., in the presence of a Fe-C or Fe-C-Cr melt. Also, other reductants like Si and Al are possible [15][16][17][18][19][20][21]. Cr bound is most difficult to reduce in spinels like MgCr 2 O 4 .…”
Section: Metals Separation and Recovery: Pyroand Hydrometallurgical Treatmentsmentioning
confidence: 99%
“…Many studies have reported on the second step of inclusion separation across the interface. However, various grades of steel need distinct slag to achieve different metallurgical tasks, such as the IF steelmaking process, slags in the refining process, and continuous casting have significantly different properties from those in pipeline steel or stainless steel manufacturing . Therefore, reconsidering the separation of inclusions across the interface is significant in understanding inclusions removed by slag in IF steel manufacturing.…”
Section: Introductionmentioning
confidence: 99%